2019
DOI: 10.3846/jbem.2019.10509
|View full text |Cite
|
Sign up to set email alerts
|

The Dynamic Impacts of Financial Development and Human Capital on Co2 Emission Intensity in China: An Ardl Approach

Abstract: This paper studies the dynamic impacts of financial development, human capital, and economic growth on CO2 emission intensity in China for the period 1978–2015, with a structural breakpoint in 1992, by employing an autoregressive distributed lag (ARDL) approach. The estimations show that there exists a long-run cointegration linkage among the variables, with three main findings. First, financial openness measured by net FDI inflows can significantly reduce CO2 emission intensity in both the short-term and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(33 citation statements)
references
References 60 publications
4
28
0
1
Order By: Relevance
“…The impact of economic growth on the consumption of energy is well established in the context of the environmental Kuznets curve (Andreoni andLevinson 2001, Richmond andKauffmann 2006). Investment in human capital not only contributes to improved productivity and economic growth but also results in positive externalities, such as improved health and environment (Schultz 1961, Becker 1994, Blackman and Kildegaard 2010, Li and Ouyang 2019. Empirical evidence shows that human capital formation can increase the absorptive capacity of an economy and reduce energy consumption (Benhabib and Spiegel 2005, Salim et al 2017, Haini 2019.…”
Section: Empirical Modeling and Datamentioning
confidence: 99%
See 1 more Smart Citation
“…The impact of economic growth on the consumption of energy is well established in the context of the environmental Kuznets curve (Andreoni andLevinson 2001, Richmond andKauffmann 2006). Investment in human capital not only contributes to improved productivity and economic growth but also results in positive externalities, such as improved health and environment (Schultz 1961, Becker 1994, Blackman and Kildegaard 2010, Li and Ouyang 2019. Empirical evidence shows that human capital formation can increase the absorptive capacity of an economy and reduce energy consumption (Benhabib and Spiegel 2005, Salim et al 2017, Haini 2019.…”
Section: Empirical Modeling and Datamentioning
confidence: 99%
“…On the one hand, human capital investment contributes to improved productivity and economic growth; on the other, it results in positive externalities such as improved health and environment (Schultz 1961, Becker 1994, Blackman and Kildegaard 2010, Li and Ouyang 2019. A large strand of literature adopts the Mincerian approach to identify aggregate externalities of human capital (through wage earnings differentials) by focusing on the estimation of the labor supply function (Mincer 1962), which was later extended by Becker (1964) with particular emphasis on return on investment in human capital (for details see Rauch 1993, Ciccone andPeri 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Similar to the research that has considered the impact of nancial development and human capital on CO2 intensity in China (Li & Ouyang, 2019), the ARDL models of this paper are as follow:…”
Section: Methodsmentioning
confidence: 99%
“…Li & Ouyang (2019) is the research that most directly related to our paper, which studies the dynamic impacts of nancial development, human capital, and economic growth on CO2 emission intensity in China for the period of 1978-2015 using the ARDL approach. Yet, Li & Ouyang (2019) does not take into consideration non-renewable energy consumption as a key factor in affecting both CO2 emissions and real GDP. Our study adds to the understanding of the literature by including non-renewable energy consumption in the framework.…”
Section: Literature Reviewmentioning
confidence: 99%
“…As human capital development improves, economic growth can reduce carbon emissions in developing countries like Ethiopia. There are several studies observed that the causal linkage between carbon dioxide emission and economic growth (Abidoye & Odusola, 2015;Andersson & Karpestam, 2013;Aye & Edoja, 2017;Nuryartono & Rifai, 2017;Nyasha, Gwenhure, & Odhiambo, 2018;Robinson, Strzepek, & Cervigni, 2013;Alam, 2014;Azomahou et al, 2005;Jardón et al, 2017;Kasperowicz, 2015;Mikayilov et al, 2018;Ru et al, 2018;Saidi & Hammami, 2015;Wang et al, 2017) and human capital with CO 2 emission (Bashir et al, 2019;Bano et al, 2018;Bashir & Susetyo, 2018;Li & Ouyang, 2019).…”
Section: Introductionmentioning
confidence: 99%